2010
DOI: 10.1146/annurev-arplant-070109-104628
|View full text |Cite
|
Sign up to set email alerts
|

The Language of Calcium Signaling

Abstract: Ca(2+) signals are a core regulator of plant cell physiology and cellular responses to the environment. The channels, pumps, and carriers that underlie Ca(2+) homeostasis provide the mechanistic basis for generation of Ca(2+) signals by regulating movement of Ca(2+) ions between subcellular compartments and between the cell and its extracellular environment. The information encoded within the Ca(2+) transients is decoded and transmitted by a toolkit of Ca(2+)-binding proteins that regulate transcription via Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
805
1
9

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,088 publications
(854 citation statements)
references
References 170 publications
14
805
1
9
Order By: Relevance
“…1,2 Though electrophysiological studies have revealed several types of Ca 2+ -permeable channels localized at the plasma membrane (PM) and vacuolar membrane (VM) in many plant species, 3 their molecular identity are still largely unknown. Homologs of the major voltage-dependent Ca 2+ channels (VDCCs) are not found in plants.…”
Section: The Tpc Family Cation Channelsmentioning
confidence: 99%
“…1,2 Though electrophysiological studies have revealed several types of Ca 2+ -permeable channels localized at the plasma membrane (PM) and vacuolar membrane (VM) in many plant species, 3 their molecular identity are still largely unknown. Homologs of the major voltage-dependent Ca 2+ channels (VDCCs) are not found in plants.…”
Section: The Tpc Family Cation Channelsmentioning
confidence: 99%
“…The Ca 2+ -dependent signaling pathways participate in many aspects of plant development and environmental responses [1][2][3]. It is generally believed that stimulus-specific calcium signals are encoded by temporally and spatially defined patterns of Ca 2+ fluctuations that result from concerted action of Ca 2+ transporters [4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In response to low-K + status, CIPK23 is activated and recruited to the plasma membrane by Ca 2+ sensors CBL1 and CBL9, and the CBL-CIPK23 complexes activate the shaker-like K + channel AKT1 for optimal K + uptake under limiting K + supply conditions [21][22][23]. Apart from controlling K + transport in roots, the CBL1-CIPK23 and CBL9-CIPK23 complexes also regulate the dual-affinity nitrate (NO 3 − ) transporter CHL1 by phosphorylation that serves as a molecular switch between low-and high-affinity NO 3 − transport modes [24]. In addition to their central regulation of ion fluxes in plant cells, CBLs play other roles in various abiotic stress adaptations.…”
Section: Introductionmentioning
confidence: 99%
“…By changing amplitude, duration, and frequency of Ca 2+ transients accordingly to environmental and developmental stimuli, plant cells interpret the source of input signals and then produce proper responses (Dodd et al, 2010;Sanders et al, 2002). Considering various responses controlled by Ca 2+ signals, plant genome is expected to encode diverse Ca 2+ sensors and mechanisms to transmit the general secondary signals to specific target components.…”
Section: Calcium Signal Regulation At the Point Of Aba And Disease Simentioning
confidence: 99%